2020
DOI: 10.1101/2020.03.11.987214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SnToxA, SnTox1andSnTox3originated inParastagonospora nodorumin the Fertile Crescent

Abstract: 18 19

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A large portion of the Asian lines were sensitive to all the NEs except Ptr ToxB. One hypothesis for this observation is that the group of Asian lines is largely comprised (84.6%) of landraces, with almost all of these originating in Iran, which is close to the center of wheat domestication and pathogen origin for P. nodorum and P. tritici-repentis (Ghaderi et al 2020;Lamari et al 2003). McDonald et al (2013) found that the SnToxA, SnTox1, and SnTox3 genes were present in 75% or more of the isolates collected from Iran.…”
Section: Discussionmentioning
confidence: 99%
“…A large portion of the Asian lines were sensitive to all the NEs except Ptr ToxB. One hypothesis for this observation is that the group of Asian lines is largely comprised (84.6%) of landraces, with almost all of these originating in Iran, which is close to the center of wheat domestication and pathogen origin for P. nodorum and P. tritici-repentis (Ghaderi et al 2020;Lamari et al 2003). McDonald et al (2013) found that the SnToxA, SnTox1, and SnTox3 genes were present in 75% or more of the isolates collected from Iran.…”
Section: Discussionmentioning
confidence: 99%
“…However, P. nodorum populations with high SnTox gene sequence diversities were not correlated with high diversity at neutral loci, suggesting that the SnTox genes were under selection by local host cultivars (McDonald et al 2013). A high frequency of the SnToxA, SnTox1 and SnTox3 genes and higher genetic diversity at neutral SSR loci of isolates collected in Iran compared to other geographic origins provided further evidence to the hypothesis that P. nodorum originated as a pathogen on wheat in the Fertile Crescent (Ghaderi et al 2020). A recent study of 197 P. nodorum isolates originating from the United States found evidence of two populations that corresponded to the Upper Midwest and South-Eastern United States (Richards et al 2019).…”
Section: Population Genetics Studies Of P Nodorummentioning
confidence: 91%
“…Epidemics of P. nodorum used to be common in all wheat-growing areas with suitable climatic condition for disease development across all six wheat-growing continents (Ficke et al 2018a;Leath et al 1993). The pathogen shares the same center of origin as its wheat host in the Fertile Crescent and probably spread during wheat germplasm exchange (McDonald et al 2012;Ghaderi et al 2020). As mentioned previously, P. nodorum and Z. tritici often cause coinfection on the host in the same field, because the asexual spores of both pathogens are spread by rain splash and prefer to grow in similar warm and humid conditions (Bearchell et al 2005).…”
Section: Infection Cycle and Epidemicsmentioning
confidence: 99%
“…However, between B. sorokiniana and these other two species, only ToxhAT is shared (20). Questions such as the order of acquisition by each species, and the origins of ToxhAT and ToxA remain (21).…”
Section: Introductionmentioning
confidence: 99%